Stimulation signal modification in a porcine model for suppression of unstable detrusor contractions - Braun, Peter-Martin; Seif, Christoph; Bross, Stephan; Martínez y Portillo, Francisco-José; Alken, Peter; Jünemann, Klaus-Peter (Urology, 2003)
Objectives - To investigate, in an experimental study, the efficacy of a different stimulation signal in a porcine model to suppress formalin-induced unstable detrusor contractions. The current mode of stimulation in peripheral nerve evaluation tests and sacral neuromodulation is based on rectangular signal shapes. Published reports, however, have revealed that up to 80% of patients do not respond to peripheral nerve evaluation stimulation. - Methods - After placement of electrodes at S3 in 12 anesthetized Göttinger minipigs, unstable contractions were induced by intravesical instillation of formalin. Ten-minute stimulation phases with a quasi-trapezoidal signal and a rectangular signal followed. An interval of 30 minutes elapsed between the two series of stimulations. The pressure values were registered on a urodynamic unit and evaluated as contractions and amplitudes per minute. Six minipigs were treated in the same way but were not stimulated and served as the control group. - Results - After formalin instillation, the average number of involuntary detrusor contractions was 3.5/min (± 0.8) and the sum of amplitudes was 7.2/min (± 1.1). Subsequent NaCl instillation and quasi-trapezoidal stimulation reduced the contractions to 0.3/min (± 0.3) and the sum of amplitudes to 0.8/min (± 0.4). A contraction rate of 1.1/min (± 0.1) and a sum of amplitudes of 5.1/min (± 2.4) were recorded under stimulation with a rectangular signal. In the control group, no significant reduction was recorded. - Conclusions - The acquired data demonstrate that quasi-trapezoidal stimulation suppresses unstable detrusor contractions in the minipig more effectively than does conventional rectangular stimulation as presently applied in sacral neuromodulation.
Gesehen am 08.03.2022